Evaluasi Kepuasan Mahasiswa Terhadap Kualitas Pelayanan Pendidikan Lembaga Pendidikan Tinggi ABC di Cikarang - Farliana Sutariah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2017)
Education is one service industry that provides services to students in need. One of Institute from Cikarang, Bekasi, West Java organized and developed the science, technology, and as a scientific community that is full of sublime imagery and educates the nation's life. The real conditions encountered by Institute is currently at in providing services to students especially on teaching staff (lecturers) as well as academic staff not yet optimal. An increase in the quality of service can be implemented using approach servequal. Servqual is a method for measuring the quality of service from a service provider. Quality of service is measured from each dimension (tangible, responsiveness, reliability, assurance, Empathize). For the result we know 5 elements spread on 4 quadrants. Quadrant 1 is spread 6 things, Quadrant II is spread 11 things, Quadrant III are spread 9 things and last Quadrant IV are spread 4 things. We investigate causes that need problem-solving on Institute by Root Cause Analyze (RCA.) Based on the results of calculation and pay attention to the real conditions, interviews with students, obtained significant complaints with the research. In this case, the Institute should improve the quality of service, both in terms of performance of teaching staff, and the number of teaching staff for teaching and learning process can be going well, so does the relationship of administration and facility staff and other supporting improved.